A preliminary study of a correlation between scores on a 6-item cognitive impairment test and a modified Bristol Activities of Daily Living Scale obtained from older women in Khayelitsha - Brodrick, Kathleen (Division of Occupational Therapy, 2017)
The absence of culturally appropriate assessment tools for the measurement of cognition and activities of daily living in an older black African population living in South Africa was the reason for embarking on the study. The purpose of the study was to develop culturally appropriate screening tools for dementia in a South African, Xhosa speaking urban black population. The aim of the study was to determine a correlation between the scores on a six item cognitive test ( 6CIT) (Brooke and Bullock 1999), and a modified Bristol Activities of Daily Living Scale (BADL) (Bucks, Ashworth, Wilcock and Siegfried 1996), in order to assess the usefulness of the cognitive test as a screening tool for dementia in black older women. A random sample of women (N=92) was drawn in an urban area (Khayelitsha) near to Cape Town, South Africa. Data were gathered with the use of three instruments. Background information was obtained from the subjects. The 6CIT was administered to the subjects. The BADL, an informant-based scale, was administered to the primary carers. The instruments were modified for local use and translated into Xhosa, the home language of the majority of residents in Khayelitsha. The results of the study showed a correlation between the scores on the two measurement instruments (r =.49745) at a 95% confidence interval. The instruments were found to be culturally appropriate for the black African older population. However, low education was a confounding factor for the cognitive test and cut-off scores, used in previous studies to detect the possible presence of early dementia, were found to be too low for this population. The modified BADL scale showed that none of the subjects were fully dependent on their carers for the performance of activities of daily living. Recommendations are that the instruments, 6CIT and modified BADL, which have been shown to be easily administered by community health workers be further validated and translated into other black South African languages. Easy to administer screening tools for dementia should be developed for detection of the disease in the population so that provision is made by health authorities and occupational therapists for treatment plans to minimise the detrimental effects of the disease on the individuals, their families and communities.